1976
DOI: 10.1172/jci108253
|View full text |Cite
|
Sign up to set email alerts
|

Parameters of the three-pool model of the turnover of plasma cholesterol in normal and hyperlipidemic humans.

Abstract: A B S T R A C T Long-term studies (32-49 wk) of the turnover of plasma cholesterol were conducted in 24 subjects. Eight subjects were normolipidemic, six had hypercholesterolemia, eight had hypercholesterolemia and hypertriglyceridemia, and two had hypertriglyceridemia alone. 10 of the hyperlipidemic patients had a definite familial disorder. In all subjects (except one for whom complete data were not available), the same three-pool model previously described gave the best fit for the data. Ml was correlated w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
14
0

Year Published

1977
1977
2013
2013

Publication Types

Select...
5
4

Relationship

2
7

Authors

Journals

citations
Cited by 60 publications
(15 citation statements)
references
References 34 publications
1
14
0
Order By: Relevance
“…The subjects were all seen at regular intervals by a nutritionist, before and during the turnover studies, to ensure compliance with the diet. The results of these initial cholesterol turnover studies, conducted before the patients received drug therapy, have been reported previously (9,(11)(12)(13).…”
Section: Methodsmentioning
confidence: 67%
See 1 more Smart Citation
“…The subjects were all seen at regular intervals by a nutritionist, before and during the turnover studies, to ensure compliance with the diet. The results of these initial cholesterol turnover studies, conducted before the patients received drug therapy, have been reported previously (9,(11)(12)(13).…”
Section: Methodsmentioning
confidence: 67%
“…The amounts of radioactivity injected (-25 uCi per subject) were measured precisely. Information about the turnover studies that were carried out before drug therapy has been reported in previous publications (9,(11)(12)(13). The repeat cholesterol turnover studies, carried out during drug therapy, were each -280 d in duration.…”
Section: Cholesterol Turnover Studies and Their Analysis [4-'4c]cholmentioning
confidence: 99%
“…The mixtures were centrifuged for 10 min at 1,500 rpm at 4°C. Exactly 1 ml of each supernate was transferred to a scintillation vial, mixed with 10 (18). Samples were obtained as well from five patients with chronic liver disease and from nine patients with chronic renal disease.…”
Section: Methodsmentioning
confidence: 99%
“…This would require further studies with apoA-I substitution. Also, our measurement of TCE and FSE does not quantify the effl ux of cholesterol from the lipid laden macrophage via ABC-transporters to HDL for subsequent elimination into the feces ( 3, 7 ), as cholesterol in atherosclerotic plaques represents merely a minute fraction of the total exchangeable cholesterol pool size ( 21,50 ). Assessment of this macrophage-specifi c RCT is currently confi ned to studies in mice ( 3 ).…”
Section: Statistical Analysesmentioning
confidence: 99%